2021
DOI: 10.3389/fphar.2021.706901
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir and Cyclosporine Synergistically Inhibit the Human Coronaviruses OC43 and SARS-CoV-2

Abstract: Remdesivir, a prodrug targeting RNA-dependent-RNA-polymerase, and cyclosporine, a calcineurin inhibitor, individually exerted inhibitory activity against human coronavirus OC43 (HCoV-OC43) in HCT-8 and MRC-5 cells at EC50 values of 96 ± 34 ∼ 85 ± 23 nM and 2,920 ± 364 ∼ 4,419 ± 490 nM, respectively. When combined, these two drugs synergistically inhibited HCoV-OC43 in both HCT-8 and MRC-5 cells assayed by immunofluorescence assay (IFA). Remdesivir and cyclosporine also separately reduced IL-6 production induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Previously, we screened drugs covered by Taiwan Health Insurance for anti-viral activity in HCoV-OC43-infected HCT-8 cells to identify those potentially suitable for repurposing as an anti-SARS-CoV-2 agent to combat COVID-19 [ 5 ]. In this continued work, we found that ciclesonide, an inhaled corticosteroid used to treat hay fever, asthma, and allergic rhinitis, increased IκBα protein levels and decreased p-p65 protein levels ( Figure 2 B) over 30 h after the infection of MRC-5 cells with HCoV-OC43.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we screened drugs covered by Taiwan Health Insurance for anti-viral activity in HCoV-OC43-infected HCT-8 cells to identify those potentially suitable for repurposing as an anti-SARS-CoV-2 agent to combat COVID-19 [ 5 ]. In this continued work, we found that ciclesonide, an inhaled corticosteroid used to treat hay fever, asthma, and allergic rhinitis, increased IκBα protein levels and decreased p-p65 protein levels ( Figure 2 B) over 30 h after the infection of MRC-5 cells with HCoV-OC43.…”
Section: Resultsmentioning
confidence: 99%
“…For the anti-coronaviral activity studies, an immunofluorescent assay was performed as described [ 5 ]. Anti-HCoV-OC43 N protein (Merck Millipore, Mab9013) and FITC-conjugated anti-mouse immunoglobulin (MP Biomedicals, Irvine, CA, USA, 55499) were used as the primary and second antibodies for anti-HCoV-OC43.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, TAC concentrations that are required to inhibit SARS-CoV-2 replication likely correlate with intolerable or toxic concentrations in humans (EC 50 of 0.2 µM equals 160 ng/ml for TAC), without even taking into account that the free fraction in traffic is only ~10%. For CsA and VCS 0.2 µM correspond to a concentration of 241 and 243 ng/ml respectively (40,69), which may come closer to peak concentrations in vivo. Moreover, the distribution of VCS over different organs might also be beneficial as concentrations in the lungs are higher than in blood (40,45).…”
Section: Discussionmentioning
confidence: 92%
“…were subjected to IFA 24 h.p.i. as described or harvested for western analyses using an antibody (MAB9013) against OC43 N protein [8,34].…”
Section: Cells Viruses Immunofluorescence Assay (Ifa) and Cytotoxicit...mentioning
confidence: 99%